Evaluation of the impact of the level of (Testosterone, Luteinizing Hormone, Follicle-Stimulating Hormone and Prolactin) on some semen parameters in infertile males - Mohammed Asaad Mahdi; Dahham L. Shwish; Nourelddin Abdulrida Almhmdi (Tikrit Journal of Pure Science)
Infertility is considered a medical condition in which the population suffers. It has several causes, including hormonal disturbance and its effect on altering sperm parameters. This study was designed to estimate the level of hormones (Testosterone, Luteinizing Hormone (LH), Follicle-Stimulating Hormone (FSH) and Prolactin) for infertility group, and the potential effect of these hormonal variables on semen parameters. The study included 50 men who were selected as an infertile group unable to conceive. In contrast, 20 healthy men were selected and able to fertilize and be considered as an control group. The level of serum Testosterone, FSH, LH and Prolactin was measured by Mini VIDAS of using ELFA method. Semen analysis was carried out according to WHO recommendations. The results showed a significant decrease in the average level of Testosterone in the infertile group (1.89±0.67ng/ml) compared with control group(4.95±1.22 ng/ml), (p<0.01). The average FSH and Prolactin level were significantly higher in the infertile group (7.15 ± 7.5 m IU/ ml , 25.56 ± 18.56 ng/ml) respectively compared with control group (2.8 ± 0.84 m IU/ml , 12.8 ± 2.51 ng/ml ) ; (P <0.05 , P < 0.01) respectively. As for the level of Luteinizing Hormone (LH), there were no statistically significant differences between infertility group and control group. The sperm count, Active motile, Sluggish motile and Normal sperm in the infertile group was less than the control group with a significant difference (P < 0.01).